Realizing the Energy Transition with Distributed Photovoltaics: A Study of High PV Penetration Grid-Edge Network Dynamics. - Pollak, Robert (Université d'Ottawa / University of Ottawa, 2022)
This paper investigates the voltage and phase dynamics of a low inertia inverter based Microgrid in islanded operation. In such case, the network is less robust to disturbances due to the lack of associated inertia within an inverter. In islanded operation, the assumption of a stiff grid is no longer valid due to the voltage and phase adjustment based on conventional droop control have a resulting effect on the power flows throughout the network where voltage and frequency stability of the network may be compromised. Other approaches neglect the network dynamics when there are power imbalances in the system and how each node is affected and if the resulting increase in demand can be met with the available power generation. This paper uses the fact that the phase dynamics of coupled inverters that employ droop control closely resemble the phase dynamics proposed by the Kuramoto model. Using this model allows the network stability to be analyzed under the true nonlinear operation. It Is observed through the strong coupling impedance of the secondary distribution transmission lines and the implementation of proportional droop control will provide an appropriate means for rural and suburban neighborhoods to operate independently, given the proportional droop gain is tuned appropriately.
Keywords: Inverters; low-voltage networks